Factors influencing firm’s environmental performance in Malaysia / Rohati Shafie - Shafie, Rohati (Institute of Graduate Studies, UiTM, 2017)
The changes in the global environmental conditions have placed great challenges to the governments, industries and societies. Business organizations are often blamed to be the sources of these environmental problems. Their role in mitigating these problems shall not be underestimated. Higher environmental performance can be translated into eco-advantage which enhances a firm’s competitiveness. Drawing from the resource-based theory, this study aimed to examine the internal and external factors influencing the environmental performance of firms certified under the ISO 14001 in Malaysia. Five hypotheses were generated by taking into consideration two internal factors (i.e. environmental policy and environmental training) and three external factors (i.e. regulatory stakeholders’ pressure, community stakeholders’ pressure and customer pressures). The total population of the study was 643 firms. Thus, this study employed census, with all the 643 firms used in the study. Five (5) face-to-face interviews and thirty (30) pilot tests from 15 firms were conducted to pretest the survey questionnaire. A total of 628 questionnaires were mailed to the respondents after excluding 15 firms from the pilot test. A total of 268 manufacturing firms responded to the questionnaires. In this research, structural equation modeling was applied to test the hypotheses…